Welche Vermögen sind vererbbar? - Zweynert, Charlotte (Historische Anthropologie, 2021)
Using a broad concept of wealth as a tool for analysis, this paper examines the wills of the writers Anna Louisa Karsch (1722–1791) and Caroline Luise von Klencke (c. 1750–1802), the grandmother and mother of Helmina von Chézy (1783–1856). It aims at determining how material and immaterial goods were transferred between women writers around 1800, what attributions and uses were thereby produced, and how persons were placed or placed themselves in the process. By using a gender-historical approach, it explores which assets were bequeathed in wills and what could be transported in testaments through and beyond material assets. In this way, a variety of intergenerational testamentary economies and a testamentary practice of (im)material (self-)positioning will be revealed.<br